T‐wave changes of cardiac memory caused by frequent premature ventricular contractions originating from the right ventricular outflow tract. (25th June 2019) - Sakamoto, Yusuke; Inden, Yasuya; Okamoto, Hiroya; Mamiya, Keita; Tomomatsu, Toshiro; Fujii, Aya; Yanagisawa, Satoshi; Shibata, Rei; Hirai, Makoto; Murohara, Toyoaki
Abstract: Introduction: Cardiac memory is recognized as altered T‐waves when the sinus rhythm resumes after an abnormal myocardial activation period that recovers slowly over several weeks. The T‐wave changes after ablation of frequent premature ventricular contractions (PVCs) as cardiac memory was not known. Objective: This study identified whether cardiac memory exists after successful ablation of PVCs from the right ventricular outflow tract (RVOT). Methods: We investigated 45 patients who underwent successful ablation of PVCs from RVOT and 10 patients who underwent unsuccessful ablation. We analyzed the amplitude of the T‐wave, QT intervals, and QRST time‐integral values of a 12‐lead electrocardiogram before ablation and 1 day, 3 days, and 1 month after ablation. Results: In the successful ablation group, the amplitude of the T‐wave and QRST time‐integral values of lead II, III, aVR, aVL, and aVF significantly changed after ablation and gradually normalized within 1 month. In addition, if the number of pre‐ablation PVCs was small, then the corresponding impact was also small. However, the greater the number of pre‐ablation PVCs, the more prominent the changes. Significant changes were not observed in the unsuccessful ablation group. Conclusion: When ablation of PVCs from RVOT was successful, primary T‐wave changes because of cardiac memory and the gradual normalization of the amplitude of the T‐wave were observed. No significant T‐wave changes were detected after unsuccessful ablation.